2017
DOI: 10.1038/s41598-017-04076-y
|View full text |Cite
|
Sign up to set email alerts
|

Lower school performance in late chronotypes: underlying factors and mechanisms

Abstract: Success at school determines future career opportunities. We described a time-of-day specific disparity in school performance between early and late chronotypes. Several studies showed that students with a late chronotype and short sleep duration obtain lower grades, suggesting that early school starting times handicap their performance. How chronotype, sleep duration, and time of day impact school performance is not clear. At a Dutch high school, we collected 40,890 grades obtained in a variety of school subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
36
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 56 publications
10
36
0
4
Order By: Relevance
“…This result coincided with the findings of previous studies that reported a similar association between sleep problems and worsened academic performance e.g. grade point or ranking [8,9,12].…”
Section: The Association Between Sleep Problems and Daytime Dysfunctisupporting
confidence: 92%
See 2 more Smart Citations
“…This result coincided with the findings of previous studies that reported a similar association between sleep problems and worsened academic performance e.g. grade point or ranking [8,9,12].…”
Section: The Association Between Sleep Problems and Daytime Dysfunctisupporting
confidence: 92%
“…Moreover, early awakening to adapt to their social schedule (e.g., for attending classes early in the morning) consequently brings about insufficient sleep especially in evening-type students. Numerous studies have reported that either insufficient sleep or later chronotype is associated with deterioration of physical health, mental health [3][4][5] and health-related quality of life [6,7] as well as worse academic performance [8][9][10][11][12] in the young population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, adolescent show time-of-day effects on attention and mood, with lowest levels in the early morning during the school day (Escribano & Díaz-Morales, 2014;Díaz-Morales, Escribano, & Jankowski, 2015). Moreover, academic achievement could be compromised if we considered chronotype, particularly for evening-type students (Goldstein, Hahn, Hasher, Wiprzycka, & Zelazo, 2007;Escribano & Díaz-Morales, 2016;Zerbini et al, 2017). Future research should take into account the neglected effects of both time of day and chronotype.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that absenteeism would peak in winter, because sick leaves are more likely to occur during the colder months, and because sleep timing, especially in late chronotypes (those who sleep late), is later in winter compared with summer (Allebrandt et al, 2014). In addition, we predicted grades would be lower in winter because of the negative effect of absenteeism on grades that has been previously described (Zerbini et al, 2017;Onyper et al, 2012).…”
mentioning
confidence: 78%